Delayed Emergence of HIV-1 Variants Resistant to 4′-Ethy Nyl-2-Fluoro-2′-Deoxyadenosine: Comparative Sequential Passage Study with Lamivudine, Tenofovir, Emtricitabine and BMS-986001. Issue 2 (February 2014) - Maeda, Kenji; Desai, Darshan V; Aoki, Manabu; Nakata, Hirotomo; Kodama, Eiichi N; Mitsuya, Hiroaki
Background: 4′-Ethynyl-2-fluoro-2′-deoxyadenosine (EFdA) contains an ethynyl moiety and the 3′-hydroxyl and exerts highly potent activity against various HIV type-1 (HIV-1) strains including multi-drug-resistant variants. Methods: Comparative selection passages against EFdA, lamivudine (3TC), tenofovir disoproxil fumarate (TDF), emtricitabine (FTC) or BMS-986001 (Ed4T) were conducted using a mixture of 11 highly multi-drug-resistant clinical HIV-1 isolates (HIV11MIX ) as a starting virus population. Results: Before selection, HIV11MIX was sensitive to EFdA with a 50% inhibitory concentration (IC50 ) of 0.032 μM, less susceptible to TDF and Ed4T with IC50 s of 0.57 and 2.6 μM, respectively, and highly resistant to 3TC and FTC with IC50 s>10 μM. IC50 s of TDF against HIV11MIX exposed to EFdA and TDF for 17 (HIV11MIX EFdA-P17 ) and 14 (HIV11MIX TDF-P14 ) passages were 8 and >10 μM, respectively, while EFdA remained active against HIV11MIX EFdA-P17 and HIV11MIX TDF-P14 with IC50 s of 0.15 and 0.1 μM, respectively. Both selected variants were highly resistant against zidovudine, 3TC, Ed4T and FTC (IC50 values >10 μM). Conclusions: The present data demonstrate that HIV11MIX developed resistance more rapidly against 3TC, FTC, TDF and Ed4T than against EFdA and that EFdA remained substantially active against TDF- and EFdA-selected variants. Thus, EFdA has a favourable resistance profile and represents a potentially promising new-generation nucleoside reverse transcriptase inhibitor.